Fracture mechanics of the endocarp of Cocos nucifera. (October 2020) - Schmier, Stefanie; Jentzsch, Maximilian; Speck, Thomas; Thielen, Marc
Abstract: Fracture mechanics and form-structure-function relationships were studied in the hierarchically structured endocarp of the coconut ( Cocos nucifera ). We mechanically tested various endocarp sample types: (1) whole endocarp; (2) arch-shaped samples prepared from the endocarp in either an equatorial or a meridional orientation; (3) small endocarp samples. The last-mentioned were tested either in their naturally grown state or with both surfaces ground coplanarly. Samples were either compression- or impact-loaded in various orientations and/or diverse setup configurations (constrained vs. un-constrained). The results establish (1) that the orientation of the whole endocarp has no significant effect on the fracture force, (2) that the orientation of arch-shaped samples affects fracture behaviour, whereas (3) test velocity does not and (4) that the compressive strength of rectangular samples is highest when applied normal to the endocarp surface. Thus, on a comparatively small scale, the endocarp is a transversely isotropic material, whereas on a larger scale, the ellipsoidal shape of the coconut compensates for weaknesses introduced by the main vascular bundles. Coconut shells are therefore good examples of the way in which potential disadvantages that concern stability and that arise from biological necessities and evolutionary constraints can be counteracted by clever material arrangements and designs. Graphical abstract: Unlabelled Image Highlights: The hard inner shell of the coconut was mechanically characterized at various length scales and velocities On a small scale the hierarchically structured coconut shell can be considered as transversely isotropic material In case of larger, arch-shaped samples orientation (equatorial vs. meridional) affects the fracture behaviour Test velocity (quasi-static vs. dynamic) does not affect fracture behaviour Mechanical disadvantages caused by biological constraints, can be compensated by clever material arrangements and designs